IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB STRES AKADEMIK SISWA MAN INSAN CENDEKIA JAMBI - Nazila Syifa Thohiroh; Muhammad Ferdiansyah; Berru Amalianita (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
Academic stress is a psychological phenomenon commonly experienced by students, related to the pressure from high academic demands and the limitations of an individual’s ability to adjust to these demands. This study aims to identify the factors causing academic stress experienced by students at MAN Insan Cendekia Jambi. Using a quantitative approach with a descriptive research design, the population of this study consists of 238 students from MAN Insan Cendekia Jambi. The sampling technique used in this study is nonprobability sampling with a purposive sampling technique, which is based on specific criteria. The criteria for this study were students categorized as experiencing moderate to severe stress, as identified through a preliminary study using the DASS-21 (Depression, Anxiety, and Stress Scale) instrument. As a result, 43 students were selected as the sample for this study. The data collection tool used in this study was a questionnaire using a Likert scale model. The results of the study indicate that academic stress among students at MAN Insan Cendekia Jambi is influenced by several main factors, both internal and external. The self-imposed factor accounted for 17.74%, followed by the factor of frustration at 17.65%. The conflict factor was identified as a cause of stress with a percentage of 17.07%. Subsequently, the pressures factor contributed 15.87%, while the physical environment factor had a percentage of 12.29%. The school-related factor followed with a percentage of 10.66%, and finally, the family factor was identified as a cause of academic stress with a percentage of 8.71%.